Astronomía y patrimonio mundial: proyecto para nominar al Observatorio de La Plata a la lista tentativa de UNESCO - Giménez Benítez, Sixto Ramón (2023)
The Observatory of La Plata has had an essential role in developing astronomy and geophysics in the southern hemisphere. Its construction was projected and integrated into the design of the city of La Plata under an innovative architectural concept of several independent buildings in an "astronomical park". From the beginning, the Observatory´s activities were driven by the ideas carried forward by the Paris Observatory at the end of the 19th Century. Furthermore, the foundation of the La Plata Observatory was linked to the impulse given by the direction of the "Bureau des Longitudes" to the missions to observe the transit of Venus in front of the Sun in 1882. The representatives of the Bureau and the province of Buenos Aires established not only the instrumental bases of the La Plata Observatory but also emphasised local collaborative work. The latter took advantage of the resources of various state departments and the training of local human resources, intertwining astronomical, geodetic and topographical skills. At the beginning of the 20th Century, the Observatory showed a clear transition from classical to modern astronomy, which falls within the period of the birth of astrophysics, with the consequent development of new research fields. Their projects were defined by integrating the Observatory into different international networks and the need to meet the foundational objectives, including training Argentine researchers. In 2004, the United Nations Educational, Scientific and Cultural Organization (UNESCO) World Heritage Center announced the "Astronomy and World Heritage" initiative to preserve historical and cultural buildings of scientific, historical, and technological relevance related to astronomy. The La Plata Observatory (1883) would be a good candidate to enter the UNESCO Cultural Heritage List with the subject "Astronomical Observatories around 1900 - from Classical Astronomy to Modern Astrophysics" together with the Hamburg Observatory (1906/12) and the Bosscha Observatory (Lembang, Java) in Indonesia (1923-1928). The three observatories would be a perfect example of the development of astronomy in the 19th-20th centuries on three continents.